2022
DOI: 10.3389/fpsyg.2022.860289
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of International Students’ Anxiety Under Online Learning During the COVID-19 Pandemic: A Cross-Sectional Study of 1,090 Chinese International Students

Abstract: ObjectiveWe conducted the following cross-sectional study to comprehensively assess the anxiety among Chinese international students who studied online during the COVID-19 pandemic and its influencing factors.MethodsQuestionnaires were distributed through “Sojump,” and a total of 1,090 valid questionnaires were collected. The questionnaire was divided into two parts: general situation and anxiety assessment of students. The former used a self-made questionnaire, and the international general GAD-7 scale was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In other words, the last external chances for Chinese international students to socialize are eliminated. According to a study conducted by Tan and other scientists, the lower frequency of socializing during the pandemic decreases the approaches for releasing stress and thus increases the possibility of all kinds of negative moods [4]. Under this circumstance, Chinese international students tend to suffer from psychological issues, and their daily lives will be severely affected.…”
Section: Socialization Problemmentioning
confidence: 99%
“…In other words, the last external chances for Chinese international students to socialize are eliminated. According to a study conducted by Tan and other scientists, the lower frequency of socializing during the pandemic decreases the approaches for releasing stress and thus increases the possibility of all kinds of negative moods [4]. Under this circumstance, Chinese international students tend to suffer from psychological issues, and their daily lives will be severely affected.…”
Section: Socialization Problemmentioning
confidence: 99%
“…The COVID-19 pandemic brought about challenges and difficulties to international students. Studies reported that international students are likely to suffer from psychological and emotional problems, which in turn negatively affect their learning [39][40][41]. In addition, an increasing number of studies have investigated the challenges of emergency online foreign language classes in the pandemic [42][43][44][45][46][47][48][49].…”
Section: Online Learning Environmentmentioning
confidence: 99%
“…Previous research on international students in degree courses reported negative influences of online environments on academic studies during the pandemic [39][40][41]. This research focused on the participants in online language courses designed specifically for international students to gain accuracy in pronunciation and fluency of speaking, understand spoken Chinese, and consolidate grammar.…”
Section: Rq 1: Characteristics Of International Students' Online Chin...mentioning
confidence: 99%
“…However, for some students, online learning can cause anxiety and stress. According to research, several factors could contribute to online learning anxiety, including technical issues (Liaw et al, 2018), isolation and lack of support (Gao et al, 2020), lack of interaction with instructors and peers (Joo, Lim, & Kim, 2019), unclear expectations and requirements , fear of technology (Alqurashi, 2019), and a perceived lack of credibility (Chou, Peng, & Chang, 2020).…”
Section: Introductionmentioning
confidence: 99%